Plasmodesmata-Involved Battle Against Pathogens and Potential Strategies for Strengthening Hosts - Liu, Jie; Zhang, Lin; Yan, Dawei (Frontiers in Plant Science, 2021)
Plasmodesmata (PD) are membrane-lined pores that connect adjacent cells to mediate symplastic communication in plants. These intercellular channels enable cell-to-cell trafficking of various molecules essential for plant development and stress responses, but they can also be utilized by pathogens to facilitate their infection of hosts. Some pathogens or their effectors are able to spread through the PD by modifying their permeability. Yet plants have developed various corresponding defense mechanisms, including the regulation of PD to impede the spread of invading pathogens. In this review, we aim to illuminate the various roles of PD in the interactions between pathogens and plants during the infection process. We summarize the pathogenic infections involving PD and how the PD could be modified by pathogens or hosts. Furthermore, we propose several hypothesized and promising strategies for enhancing the disease resistance of host plants by the appropriate modulation of callose deposition and plasmodesmal permeability based on current knowledge.